2011
DOI: 10.1088/0004-637x/736/1/34
|View full text |Cite
|
Sign up to set email alerts
|

Low-Velocity Collisions of Centimeter-Sized Dust Aggregates

Abstract: Collisions between centimeter-to decimeter-sized dusty bodies are important to understand the mechanisms leading to the formation of planetesimals. We thus performed laboratory experiments to study the collisional behavior of dust aggregates in this size range at velocities below and around the fragmentation threshold. We developed two independent experimental setups with the same goal to study the effects of bouncing, fragmentation, and mass transfer in free particle-particle collisions. The first setup is an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
126
4
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(145 citation statements)
references
References 20 publications
10
126
4
5
Order By: Relevance
“…Anyhow, it is questionable if the onset of fragmentation is totally mass independent. Recent experiments by Beitz et al (2011) and Schräpler et al (2012) have shown that dust aggregates larger than one centimeter fragment at velocities slightly lower than 1 m s −1 . This, however, does not change the picture qualitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Anyhow, it is questionable if the onset of fragmentation is totally mass independent. Recent experiments by Beitz et al (2011) and Schräpler et al (2012) have shown that dust aggregates larger than one centimeter fragment at velocities slightly lower than 1 m s −1 . This, however, does not change the picture qualitatively.…”
Section: Discussionmentioning
confidence: 99%
“…For solid bodies, this transition occurs around 100 m in size. Values of Q * ∼ 10 7 erg/g are often taken as typical for asteroids, and experimentally obtained values for small grains (mm to cm sizes) can be several orders of magnitude smaller (Blum & Münch 1993;Beitz et al 2011). Figure 1 shows the critical energy for splitting predicted by Eq.…”
Section: Minimum Fragment Size In a Single Collisionmentioning
confidence: 99%
“…(6)) is shown for η = 10 −3 (dotted) and η = 1 (dashed). The solid curves correspond to catastrophic fragmentation of aggregates (Beitz et al 2011), and ice and basalt (Benz & Asphaug 1999), showing both the strength-dominated (small sizes) and self-gravity dominated regimes (large sizes).…”
Section: Minimum Fragment Size In a Single Collisionmentioning
confidence: 99%
See 1 more Smart Citation
“…been shown by impacts of cm-size aggregates at velocities of up to 2 m/s (Beitz et al 2011), 1.5−6 m/s (Kothe et al 2010), or even 60 m/s (Teiser & Wurm 2009b). These experiments show that as soon as the destruction of a projectile is possible, some mass might be transferred to a somewhat larger target, leading to net growth.…”
Section: Resultsmentioning
confidence: 63%